Zero-tillage farming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
To prevent medium and large-scale farmers in the tropics from losing their fragile land through erosion and other soil. degrading factors scientists and agricultural engineers of the International Institute of Tropical Agriculture (IITA) are of the...